Anticipating the clinical adoption of regenerative medicine: building institutional readiness in the UK. (January 2018) - Gardner, John; Webster, Andrew; Barry, Jacqueline
This perspective paper examines the challenges of implementing regenerative medicine (RM) therapies within hospitals and clinics. Drawing on recent work in the social sciences, the paper highlights dynamics within existing healthcare systems that will present both hindrances and affordances for the implementation of new RM technologies within hospitals and clinics. The paper argues that identifying suitable locations for cell- and gene-therapy treatment centers requires an assessment of their institutional readiness for RM. Some provisional criteria for assessing institutional readiness are outlined, and the paper will suggest that it is necessary to begin developing a program for the phased introduction of RM in the longer term.